Gestión presupuestaria en el Gad municipal del cantón Baba durante el periodo 2021-2022. - Salvatierra Morales, Genesis Elizabeth (2023)
Budget management must be carried out as part of the compliance of public institutions, which must comply with parameters established by Ecuadorian laws, and the internal policies of each of the institutions according to the functions for which they were created, despite This is the Municipal GAD of Baba, during the period 2021-2022; did not comply with some of these parameters, which does not allow citizens to know if the fulfillment of the established goals and objectives was fully met, leaving in this case a gap of doubts and questions without answers about what was planned and executed during this period. The lack of policies for budget management caused that during these two periods of administrative management the development of the activities carried out is not part of the knowledge of the new administration, since not having the necessary information does not allow them to know what the programs are. that are active or in the process of completion, allowing new plans and budgets to be developed in a concatenated manner to previous programs.